Whatever happened to Sunday dinner? : a year of Italian menus, with more than 250 recipes, that celebrate family - Caponigri, Lisa (Sterling Epicure, 2012)
"Whatever Happened to Sunday Dinner? came from author Lisa Caponigri's belief that the family who eats together stays together. The book is filled with 52 menus--one menu for each Sunday of the year--that are meant to be cooked together as a family and then enjoyed together. All the classics--lasagne, polenta, stuffed peppersveal piccata, Pasta all'Amatriciana, risotto all Milanese, crostini of all sorts--fill the pages, but there are many surprises like, chicken in panna, Woodman's pasta, Italian French Fries, not to mention all the personal family treasures, like Margarita's Casateddi, Grandma Franco's Fedora, Nana's Strufoli, Grandma Caponigri's Ragu Sauce...that make it unbeatable. Lisa originally self-published these recipes. Now, we've completely re-edited them, making them user friendly for both the professional and nonprofessional cook alike. More than 100 new color photographs come from Guy Ambrosino. The food was styled by former Gourmet magazine editor Kate Winslow"--